Bandwidth extension of speech based on non-linear transformation and automatic gain control - Zaw Zaw Aung (2008)
Propose a postprocessing technique to recover the missing highband frequency components lost during low pass filtering in band-limited narrowband speech signals, based on automatic gain control of the non-linear mapping functions for highband excitation.